Remote sensing approaches for land use and land surface temperature assessment: a review of methods. (3rd July 2017) - Ayanlade, Ayansina
ABSTRACT: Selection of appropriate data and methods for environmental change assessment is highly central in any remote sensing research project. This study assessed various land use/land cover change (LUCC) methods and tested the accuracy of prominent classification methods and their implications on land surface temperature (LST) change estimation. Niger Delta of Nigeria was used as a case study. The study concluded that, though no single method can be applied to all cases and regions, there are some factors that determine the remote sensing methods to be used in both LST and LUCC change analysis. Such factors include the spatial, temporal, spectral and radiometric resolutions of satellite image and environmental factors. Therefore, this paper evaluated methods used in earlier studies to assess, monitor and model LUCC impacts on LST. The paper concludes by proposing the use of two or more methods in any LUCC–LST research project. This is because, all remote sensing methods are not totally right, but some are useful, thus, the methods should be viewed as complementary.